1987
DOI: 10.1161/01.hyp.10.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Thallium-201 stress imaging in hypertensive patients.

Abstract: SUMMARY To assess the potential effect of hypertension on the results of thallium-201 stress imaging in patients with chest pain, 272 thallium-201 stress tests performed in 133 hypertensive patients and 139 normotensive patients over a 1-year period were reviewed. Normotensive and hypertensive patients were similar in age, gender distribution, prevalence of cardiac risk factors (tobacco smoking, hyperlipidemia, and diabetes mellitus), medications, and clinical symptoms of coronary disease. Electrocardiographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 48 publications
0
11
0
2
Order By: Relevance
“…This is particularly true in the presence of left ventricular hypertrophy, which makes an EET uninterpretable. 2 Unfortunately, alternative stressing procedures, such as exercise radionuclide angiography 3 and thallium-201 stress imaging, 4 were found to be inadequate screening tests for CAD because of the frequent occurrence of false-positive responses.…”
mentioning
confidence: 99%
“…This is particularly true in the presence of left ventricular hypertrophy, which makes an EET uninterpretable. 2 Unfortunately, alternative stressing procedures, such as exercise radionuclide angiography 3 and thallium-201 stress imaging, 4 were found to be inadequate screening tests for CAD because of the frequent occurrence of false-positive responses.…”
mentioning
confidence: 99%
“…They found that 20 of the 38 patients (53%) had perfusion abnormalities which were responsible for a decrease in coronary reserve, myocardial damage, or both, due to long-standing systemic hypertension or to aortic regurgitation. They also pointed out that the mechanism of the perfusion abnormalities in these patients with arteritis was the same as that seen in patients with hypertrophic cardiomyopathy [16] or hypertensive heart disease [17].…”
Section: Discussionmentioning
confidence: 70%
“…Для гипертонического поражения сердца типично снижение ранней скоро-сти диастолического наполнения (е'), определенной без выраженных симптомов, характерных для ИБС с окклюзией. Если результаты ЭКГ с физической нагрузкой положительны или не могут быть интерпре-тированы (неоднозначны), то для надежной диагно-стики ишемии миокарда требуется методика, позволя-ющая визуализировать появление ишемии, например, стресс-МРТ сердца, перфузионная сцинтиграфия или стресс-эхокардиография [178][179][180]. Индуцированные стрессом нарушения подвижности стенок желудочка высокоспецифичны для стеноза эпикардиальных артерий, подтвержденного ангиографически.…”
Section: расширенное обследование (обычно проводится соответствующимиunclassified